2019
DOI: 10.3390/acoustics1030027
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning the Acoustical Performance of an Open Office Space Following the Latest Healthy Building Standard: A Case Study

Abstract: Healthy building design guides are cogent and necessary. While elements that contribute to healthy buildings are multifactorial, the perception of sound versus noise is subjective and difficult to operationalize. To inform the commissioning process, the acoustics in an open office was examined following the first international building certification system that focuses on the well-being of occupants. Results highlight the role facility managers play in ensuring acoustical quality and offer suggestions to optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The problems and peculiarities of the open-plan offices revealed during the research match the results of the questionnaire, which was evaluated by descriptive statistical analysis and used in the conception; they confirm that the most significant disadvantages of spatial design are the noisy work environment and the lack of private space. Research has confirmed that work efficiency, workplace comfort, and health are influenced by two factors that have been addressed in several previous studies [1][2][3][4]; however, their connection to community and recreational spaces has no comprehensive studies. One peculiarity of the planning was that office-level problems had to be solved only by redesigning the given spaces: relocating noise inducing and distracting activities, along with designing adequate visual and acoustic separation, became extremely important.…”
Section: Design Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…The problems and peculiarities of the open-plan offices revealed during the research match the results of the questionnaire, which was evaluated by descriptive statistical analysis and used in the conception; they confirm that the most significant disadvantages of spatial design are the noisy work environment and the lack of private space. Research has confirmed that work efficiency, workplace comfort, and health are influenced by two factors that have been addressed in several previous studies [1][2][3][4]; however, their connection to community and recreational spaces has no comprehensive studies. One peculiarity of the planning was that office-level problems had to be solved only by redesigning the given spaces: relocating noise inducing and distracting activities, along with designing adequate visual and acoustic separation, became extremely important.…”
Section: Design Methodsmentioning
confidence: 70%
“…The concept of open-plan offices has been addressed in several studies in the past and is still addressed today [1][2][3][4]. According to Candido's research, only 4 scientific articles on the Scopus platform examined the topic in 1999counting articles where the term 'open-plan office' was included in the title, abstract or keywords of the research -in 2018 there were fifteen times as many, 60 studies on the topic [1].…”
Section: Research Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise generated by any means of transportation is one of the main environmental damage factors with adverse effects on comfort. In line with that, Kim et al [8] stated that noise is unwanted sound because it is not in accordance with space and time so that it can cause interference with human comfort and health. The open roadside building's design has evidence that noise causes a lack of privacy, affects the level of disturbance, and employee dissatisfaction.…”
Section: Introductionmentioning
confidence: 87%
“…This is especially important because older buildings were often built to less stringent standards than modern ones. Consequently, they often do not meet today's health standards [ 135 ]. For example, by adopting an appropriate HVAC system can improve ventilation and help prevent the spread of respiratory illness in indoor spaces.…”
Section: Dna Framework Of Healthy Building Developmentmentioning
confidence: 99%